NUMERICAL MODELING OF A PARABOLIC TROUGH SOLAR COLLECTOR AT BOUZARÉAH, ALGERIA - Ghodbane, M; Boumeddane, B (جامعة الوادي - university of el oued, 2015)
In this paper, we are interested in numerical study conversion of the solar energy into thermic energy using a Parabolic through Collector at Bouzaréah, Algeria. Water is used as a heat carrier fluid. A mathematical model drawn from the energy balance equation applied to the absorber tube, it was solved by the finite difference method. A computer program was developed to solve our problem. MATLAB used as a tool for simulation. This program allows calculating the change in thermal efficiencies, the absorber tube temperatures, the fluid temperatures, the glass temperatures and the coefficient of heat loss. The results are very honorable and encouraging, where the thermal efficiency of the concentrator had passed 60%.
Article
Keywords: Parabolic through Collector, outlet temperature, fluid, numerical simulation.